ANALISIS PENGETAHUAN DOSEN DAN MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL - Yudhawasthi, Ciwuk Musiana; Rifaldi Akbar, Moh.; Dwi Lestari, Anita; Nabawiyah, Dinda; Faustina, Helena (Universitas Islam Negeri Alauddin Makassar, 2023)
Cases of sexual violence are quite common in the higher education environment. In early 2023, as part of the implementation of Permendikbudristek No. 30 of 2021, which is also a